Determinant nucleotides of yeast tRNA(Asp) interact directly with aspartyl-tRNA synthetase. - Rudinger, J (1992)
The interaction of wild-type and mutant yeast tRNA(Asp) transcripts with yeast aspartyl-tRNA synthetase (AspRS; EC 6.1.1.12) has been probed by using iodine cleavage of phosphorothioate-substituted transcripts. AspRS protects phosphates in the anticodon (G34, U35), D-stem (U25), and acceptor end (G73) that correspond to determinant nucleotides for aspartylation. This protection, as well as that in anticodon stem (C29, U40, G41) and D-stem (U11 to U13), is consistent with direct interaction of AspRS at these phosphates. Other protection, in the variable loop (G45), D-loop (G18, G19), and T-stem and loop (G53, U54, U55), as well as enhanced reactivity at G37, may result from conformational changes of the transcript upon binding to AspRS. Transcripts mutated at determinant positions showed a loss of phosphate protection in the region of the mutation while maintaining the global protection pattern. The ensemble of results suggests that aspartylation specificity arises from both protein-base and protein-phosphate contacts and that different regions of tRNA(Asp) interact independently with AspRS. A mutant transcript of yeast tRNA(Phe) that contains the set of identity nucleotides for specific aspartylation gave a phosphate protection pattern strikingly similar to that of wild-type tRNA(Asp). This confirms that a small number of nucleotides within a different tRNA sequence context can direct specific interaction with synthetase.